Results of Application of Clinpro White Varnish® and Tooth Mousse® during the Enamel Mineral Maturation and its Focal Demineralization (Global Journal of Science Frontier Research, 2021)
According to some authors, the final maturation of tooth enamel occurs in 1-2 years after eruption, and then for 2-3 years this process continues in just the fissure area. Full-fledged mineralization during this period is carried out due to the absorption of minerals from saliva, especially in respect to fluorine, calcium and phosphorus ions. As a result of the course of prophylactic treatment with Clin Pro White Varnish® and Tooth Mooth®, an activation of remineralization process was observed ended with the stabilization of the process or complete remineralization in the junior (6-7 years old) and the middle school group children (12-13 years old), which was confirmed by the obtained indices of the "DiagnodentKaVo" laser fluorometry test and the colorimetric test. The use of these preparations is a convenient and effective method in these age groups of children during the preventive treatment provision.
Keywords: remineralization; laser fluorometry; colorimetric test; schoolchildren